Seawater-based BaA detection method

The electrochemical immunosensor is constructed by graphitized carboxylated multi-walled carbon nanotube-polydopamine composite modified electrode, which solves the problems of high cost and complex operation of benzo[a]anthracene detection method in seawater, and achieves efficient and economical detection effects.

CN119619247APending Publication Date: 2025-03-14BEIBU GULF UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411766085.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing benzo[a]anthracene detection method in seawater has problems such as high detection cost, complex operation, poor reproducibility of results, and special requirements for substrate materials and instruments.

Method used

The electrochemical immunosensor platform was constructed by graphitizing carboxylated multi-walled carbon nanotube-polydopamine composite modified electrodes, and the content of benzo[a]anthracene was detected by differential pulse voltammetry.

Benefits of technology

It achieves low detection limit (0.35ng·ml-1), high recovery rate (94.18%~99.11%) and low relative standard deviation (RSD ≤2.71%), while simplifying the operation process and reducing the detection cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119619247A_ABST
    Figure CN119619247A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of seawater detection, and particularly relates to a seawater-based BaA detection method which comprises the following steps: S1, preparing a graphitized carboxylated multi-walled carbon nanotube-polydopamine composite modified electrode; s11, dissolving 0.03 g of polydopamine in a dilute acetic acid solution (1% v / v) to prepare a 0.03 mg.ml <-1 > polydopamine acetic acid solution, and storing the polydopamine acetic acid solution in an environment of 4 DEG C for later use; s12, dispersing 0.02 g of the graphitized carboxylated multi-walled carbon nanotubes in 10 ml of a PBS buffer solution with the pH value of 7, placing in an ultra-speed centrifuge at the room temperature, centrifuging for 10 minutes at the rotating speed of 15000 r / min, then performing ultrasonic treatment for 1.5 hours in an ultrasonic oscillator, and stirring for 1 hour at the room temperature; compared with a traditional spectrum method and a traditional chromatography method, the method has the remarkable advantages in the aspects of operation convenience, cost economy, result accuracy, preparation simplicity, short analysis time and the like, and it is fully proved that the immunosensor has huge application potential in the field of seawater BaA detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of seawater detection, in particular to a method for detecting seawater-based BaA. Background Art

[0002] The ocean is a key component of the earth's ecosystem. The quality of seawater is directly related to the survival and reproduction of many organisms and the sustainable use of marine resources by humans. However, with the acceleration of industrialization and the increasing frequency of human activities, the pollution of seawater by polycyclic aromatic hydrocarbons has become increasingly serious. Polycyclic aromatic hydrocarbons (PAHs) are organic compounds composed of two or more single aromatic rings or fused aromatic rings. They mainly come from transportation leakage, incomplete combustion, and emissions of organic substances such as coal and oil. This compound is widely present in the environment mainly through air and water. Due to its potential toxicity, persistence and wide environmental distribution, it has become a type of pollutant that has attracted much attention.

[0003] At present, the detection methods for benz[a]anthracene in seawater mainly focus on two categories: spectroscopy and chromatography:

[0004] Au nanospheres and Au-Ag alloy nano-sea urchins were prepared by reducing chloroauric acid, and the mixed colloidal solution of the two was used as the substrate for surface enhanced Raman scattering to detect the BaA content in water, with a detection limit of 2.92 nmol - L -1 The use of this method can enhance the Raman scattering signal by 104 to 106 times. It is simple to operate and has a fast analysis speed. However, this method is highly dependent on the properties and structure of the substrate. Slight differences in the substrate will lead to poor reproducibility of the results. At the same time, it has special requirements for substrate materials and instruments, so the detection cost is high.

[0005] A test scheme for the simultaneous rapid analysis of benz[a]anthracene and 9.10-dimethylanthracene was established by using a fixed wavelength synchronous fluorescence method, and the detection limit of benz[a]anthracene was 5 ng. - mL -1 This method can obtain a strong fluorescence signal when the concentration of benzo[a]anthracene is low; however, the detection requires high-quality fluorescence spectrophotometers and other instruments and equipment, which increases the detection cost to a certain extent. At the same time, the instrument operation is relatively complicated and the instrument maintenance is relatively strict. The slight interfering substances in the test samples and turbid and opaque samples will have a great impact on the test results, so a complex preliminary pretreatment process is required.

[0006] Therefore, in view of the above problems, a detection method for seawater-based BaA is proposed. Summary of the invention

[0007] 1. Technical issues to be solved

[0008] In view of the shortcomings of the prior art, the present invention provides a method for detecting seawater-based BaA to solve the problems raised in the background technology.

[0009] (II) Technical solution

[0010] To achieve the above object, the present invention provides the following technical solution: a method for detecting seawater-based BaA, comprising the following steps:

[0011] S1, preparation of graphitized carboxylated multi-walled carbon nanotube-polydopamine composite modified electrode;

[0012] S11, 0.03 g of polydopamine (PDA) was dissolved in dilute acetic acid solution (1% v / v) to prepare 0.03 mg - ml-1 polydopamine acetate solution, stored at 4°C for later use;

[0013] S12, dispersing 0.02 g of graphitized carboxylated multi-walled carbon nanotubes (GR-MWCNTs-COOH) in 10 ml of PBS buffer at a pH of 7, centrifuging at 15,000 r / min for 10 minutes in an ultracentrifuge at room temperature, then ultrasonicating in an ultrasonic oscillator for 1.5 hours, and stirring at room temperature for 1 hour;

[0014] S13, polishing a glassy carbon electrode (GCE) with a diameter of 3 mm with aluminum oxide (Al2O3) powder of 1.0 μm, 0.3 μm, and 50 nm particle sizes to a bright surface, and then ultrasonically treating it for 30 s;

[0015] S14, placing the glassy carbon electrode (GCE) in a 0.5 mol-L-1 sulfuric acid solution, scanning the glassy carbon electrode (GCE) several times from -0.3 V to +1.5 V using cyclic voltammetry (CV) until the curves completely overlap, then rinsing with ultrapure water and drying with nitrogen;

[0016] S15, in the presence of 0.1 mol-L -1 Potassium chloride (KCl) and 5mmol-L -1 Cyclic voltammetry (CV) was performed in a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferrate (K3[Fe(CN)]6) at -0.2 V to 0.6 V until the redox peaks were symmetrical and stable and the potential difference was about 90 mV.

[0017] S16, drop a total of 5.0 μL of graphitized carboxylated multi-walled carbon nanotubes vertically on the surface of a glassy carbon electrode (GCE), place it in a drying oven at 26°C until the surface is dry, then add 10 μL of an equal amount of a mixture of carbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) dropwise, place it at 4°C for 2h, drop 5 μL of polydopamine (PDA) acetic acid solution on the electrode surface, dry it at room temperature, and obtain a graphitized carboxylated multi-walled carbon nanotube composite film;

[0018] S2, construction of electrochemical immunosensor platform;

[0019] S21, drop 10 μL of benz[a]anthracene antibody on the surface of graphitized carboxylated multi-walled carbon nanotube composite film, incubate in a 37°C drying oven for 2 h, then drop 5 μL of 3% bovine serum albumin (BSA) solution for 40 min to block the remaining active sites and avoid nonspecific adsorption, thereby allowing the immunosensor to specifically recognize benz[a]anthracene;

[0020] S22, placing the obtained immunosensor modified with the graphitized carboxylated multi-walled carbon nanotube composite film in a 4° C. environment for standby use;

[0021] S3, immunoassay steps for the detection of benz[a]anthracene;

[0022] S31, the immunosensor modified with graphitized carboxylated multi-walled carbon nanotube composite film was placed in 0.1 mol - L -1 Potassium chloride (KCl) and 5mmol - L -1 In a PBS (pH = 7.0) buffer solution environment of tripotassium hexacyanoferrate (K3[Fe(CN)]6), the potential range was -0.2 to -0.6 V and the scan rate was 0.05 Vs -1 Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed under the conditions of to characterize the electrochemical performance and immune response of the modified immunosensor;

[0023] S32. Before measurement, 10 μL of different concentration gradients (0.1 ng-mL -1 ~100ng-mL -1 ) was titrated onto the modified immunosensor surface and incubated at 37 °C for 30 min;

[0024] S33, immersing the working electrode, the counter electrode and the reference electrode in the electrolyte, and recording the peak current Ip of different benz[a]anthracene concentrations between -0.2V and 0.6V by differential pulse voltammetry (DPV), wherein the amplitude is set to 50mV;

[0025] S34. A linear relationship is established by analyzing the relationship between Ip and the corresponding benzo[a]anthracene standard concentration to obtain a calibration curve.

[0026] Preferably, based on the S2, in 0.1 mol - L -1 Potassium chloride (KCl) and 5mmol - L -1 In a PBS (pH=7.0) buffer solution environment of tripotassium hexacyanoferrate (K3[Fe(CN)]6), the electrochemical properties of different materials on the electrode surface were characterized by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS).

[0027] Preferably, the graphitized carboxylated multi-walled carbon nanotube / polydopamine / benzo[a]anthracene / bovine serum albumin / glassy carbon electrode is subjected to cyclic voltammetry scanning at different scanning rates, and the peak current increases with the increase of scanning rate ... -1 In the scan rate range, the current and the square root of the scan rate show a good linear relationship, which indicates that the electron transfer in the electrode reaction is controlled by the diffusion process;

[0028] By Randles-Sevcik equation:

[0029] Ip=2.69×10 5 AD 1 / 2 n 3 / 2 v 1 / 2 c (1)

[0030] The effective surface area of ​​the electrode during the reaction can be calculated, where

[0031] Ip is the peak current (μA);

[0032] A is the effective surface area of ​​the electrode (cm 2 );

[0033] D is the diffusion coefficient (cm 2- s -1 );

[0034] n is the number of moles of transferred electrons in the electrostatic strain variation coefficient;

[0035] v is the rate of change of potential (Vs -1 );

[0036] c is the concentration of ferrocyanide (mmol - L -1 );

[0037] Where D = 0.72 × 10 -5 cm 2-s -1 , n=1,v=0.05Vs -1 , c = 5 mmol - L -1 The above formula is used to calculate that the effective areas of the glassy carbon electrode, the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes, and the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and polydopamine are 0.361, 0.505, and 1.053 cm2, respectively. It can be concluded that the synergistic effect of the two nanomaterials, graphitized carboxylated multi-walled carbon nanotubes and polydopamine, significantly increases the electrode surface area involved in the reaction and improves the sensitivity of the electrochemical detection method.

[0038] Preferably, to verify whether the glassy carbon electrode is successfully modified, differential pulse voltammetry is performed on an unmodified glassy carbon electrode, an electrode modified with graphitized carboxylated multi-walled carbon nanotubes, an electrode modified with polydopamine, and an electrode to which anti-benz[a]anthracene antibodies and bovine serum albumin are added, respectively. On this basis, anti-benz[a]anthracene antibodies and bovine serum albumin are drop-coated one by one. Both the anti-benz[a]anthracene antibodies and bovine serum albumin are proteins, which play an inhibitory role in the electron transfer process. Therefore, the peak current after differential pulse voltammetry detection decreases one by one. Based on the properties of the modified material and the detection mechanism, the successful modification of the glassy carbon electrode is verified.

[0039] Preferably, based on S3, 10 μL of anti-benz[a]anthracene antibody solutions of different concentrations were incubated in the same experimental environment, and the anti-benz[a]anthracene antibody was drop-coated on the surface of the polydopamine nanoparticle composite film and placed in 0.1 mol - L -1 Potassium chloride (KCl) and 5mmol - L -1 Differential pulse voltammetry was performed in a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferrate (K3[Fe(CN)]6). As the concentration of anti-benz[a]anthracene antibody increased, the peak current gradually decreased. When the concentration of anti-benz[a]anthracene antibody was 100 μg-mL- 1 , the peak current reached the lowest value, and then as the concentration of anti-benz[a]anthracene antibody continued to increase, the peak current also increased. This is due to the limited active sites on the surface of the polydopamine nanoparticle composite membrane. The concentration of anti-benz[a]anthracene antibody was 100 μg-mL- 1 When the antibody concentration on the electrode surface reaches saturation, the concentration of anti-benz[a]anthracene antibody is 100 μg-mL- 1 The optimal concentration for the experiment.

[0040] Preferably, based on S2, the detection principle of the electrochemical immunosensor is that the antibody-antigen reaction on the electrode surface causes changes in electron transfer, and the current generated on the electrode surface reflects the content of benz[a]anthracene. Therefore, when using differential pulse voltammetry for detection, the higher the benz[a]anthracene content in the sample to be tested, the lower the peak current. However, since benz[a]anthracene is a polycyclic aromatic hydrocarbon, it is easily electro-oxidized at high potential to promote electron transfer, which can increase the detection current and thus obtain a wider detection range. Therefore, the oxidation peak of differential pulse voltammetry is selected to quantitatively analyze the content of benz[a]anthracene. As an insulating electrical substance, benz[a]anthracene increases the transmission resistance during the immune reaction. Therefore, as the concentration of benz[a]anthracene increases, the peak current decreases. According to the fitting curve, it can be concluded that in the range of 5-100ng-ml- 1 In the range of , the response current is linearly related to the concentration of benz[a]anthracene, where the linear equation is I = 591.32-4.353C and the correlation coefficient is R 2 =0.996, in order to further derive the detection limit formula, the following deduction is made:

[0041] Standard Deviation:

[0042]

[0043] Assume that the detection limit concentration is C LOD , the corresponding measurement signal is

[0044] I LOD = k*C LOD +b (3)

[0045] Signal-to-Noise Ratio:

[0046]

[0047] When SNR = 3, that is,

[0048]

[0049] The detection limit formula can be calculated from the above formulas (2) to (5):

[0050]

[0051] in:

[0052] n is the number of parallel measurements of blank samples

[0053] I 0i is the blank sample signal value

[0054] k is the slope of the calibration equation

[0055] b is the intercept of the calibration equation

[0056] The blank sample was measured 11 times in parallel, and the detection limit was 0.35 ng-ml -1 , RSD = 0.52%, which is far lower than the international residual standard of benz[a]anthracene.

[0057] (III) Beneficial effects

[0058] Compared with the prior art, the present invention provides a method for detecting seawater-based BaA, which has the following beneficial effects:

[0059] 1. The present invention successfully constructed a new type of immunosensor by fixing anti-BaA on the GR-MWCNTs-COOH / PDA nanocomposite film. GR-MWCNTs-COOH was used as the fixing bracket of the antibody to reduce nonspecific adsorption. The active groups of PDA were combined with the antibody to further enhance the fixing effect of the antibody on the electrode surface and improve the transmission efficiency of the detection signal. Under the optimal experimental conditions, the detection limit was 0.35 ng·ml -1 The relative standard deviation (RSD) is 0.52%. In the detection application of BaA in actual seawater, the recovery rate is between 94.18% and 99.11%, and RSD≤2.71%.

[0060] 2. Compared with traditional spectroscopy and chromatography, the present invention has significant advantages in terms of operational convenience, cost-effectiveness, result accuracy, ease of preparation and short analysis time, which fully confirms that the immunosensor has great application potential in the field of seawater BaA detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0062] Figure 1 is a schematic diagram of the detection mechanism of the electrochemical immunosensor of the present invention;

[0063] Figure 2 It is a process flow chart of preparing the graphitized carboxylated multi-walled carbon nanotube composite film of the present invention;

[0064] Figure 3 It is a schematic diagram of the specific recognition principle of antigen and antibody in the present invention;

[0065] Figure 4The scanning electron microscope images of the graphitized carboxylated multi-walled carbon nanotubes (A), polydopamine nanoparticles (C), and graphitized carboxylated multi-walled carbon nanotube composite film (E) at a magnification of 20kx and the scanning electron microscope images of the graphitized carboxylated multi-walled carbon nanotubes (B), polydopamine nanoparticles (D), and graphitized carboxylated multi-walled carbon nanotube composite film (F) at a magnification of 100kx in the present invention;

[0066] Figure 5 The cyclic voltammetry diagrams (A) of the five different immunosensors of the present invention and the immunosensors at different scanning rates (0.01 V·s -1 ~0.13V·s -1 ) under cyclic voltammetry (B);

[0067] Figure 6 is a differential pulse voltammetry diagram of five different immunosensors in the present invention;

[0068] Figure 7 1 is an electrochemical impedance spectrum (A) of five different immunosensors of the present invention and an electrochemical impedance spectrum (B) of a glassy carbon electrode;

[0069] Figure 8 The present invention uses differential pulse voltammetry to optimize the electrochemical immunosensor to determine the concentration of the primary antibody (0, 20, 40, 60, 80, 100, 120 and 140 μg ml -1 ) curve graph of the optimal conditions (A) and line graph of peak current at different antibody concentrations (B);

[0070] Fig. 9 In the present invention, 100 μg ml was recorded in the range of pH 4.0 to 8.0. -1 Differential pulse voltammetry of benzo[a]pyrene antibody, the relationship between the peak current of differential pulse voltammetry and the pH value of the test solution (A) and the line graph of the peak current at different pH values ​​of the supporting electrolyte (B);

[0071] Fig.10 In the present invention, 1 mmol L -1 (A), 5mmol L -1 (B), 10mmol L -1 (C) and 15 mmol L -1 (D) Cyclic voltammetry curves of potassium hexacyanoferrate (K3[Fe(CN)6]) before and after immune reaction at different concentrations;

[0072] Fig.11The differential pulse voltammetry curves (A) of the immunosensor proposed in the present invention for different concentrations of benz[a]anthracene antibodies (5, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100 ng·ml-1) and the calibration curves (B) of the immunosensor for different concentrations of benz[a]anthracene antibodies;

[0073] Fig.12 In the present invention, 50ng·ml -1 Peak current diagram after adding 20-fold concentration of anthracene, benzopyrene, fluoranthene, naphthalene and phenanthrene to benzo[a]anthracene antibody (A) and the peak current diagram at 50 ng·ml -1 Peak currents of six batches of different electrodes in benz[a]anthracene antibody solution (B);

[0074] Fig.13 The peak current diagram of the same modified electrode tested for 6 consecutive times in the present invention (A) and the peak current diagram of the same modified electrode tested for 30 days (B). DETAILED DESCRIPTION

[0075] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] Specific examples are given below.

[0077] See also Figure 1-Figure 13 The present invention provides a method for detecting seawater-based BaA, comprising the following steps:

[0078] S1, preparation of graphitized carboxylated multi-walled carbon nanotube-polydopamine composite modified electrode;

[0079] S11, dissolving 0.03 g of polydopamine (PDA) in a dilute acetic acid solution (1% v / v) to prepare a 0.03 mg-ml-1 polydopamine acetic acid solution, and storing it at 4° C. for later use;

[0080] S12, dispersing 0.02 g of graphitized carboxylated multi-walled carbon nanotubes (GR-MWCNTs-COOH) in 10 ml of PBS buffer at a pH of 7, centrifuging at 15,000 r / min for 10 minutes in an ultracentrifuge at room temperature, then ultrasonicating in an ultrasonic oscillator for 1.5 hours, and stirring at room temperature for 1 hour;

[0081] S13, polishing a glassy carbon electrode (GCE) with a diameter of 3 mm with aluminum oxide (Al2O3) powder of 1.0 μm, 0.3 μm, and 50 nm particle sizes to a bright surface, and then ultrasonically treating it for 30 s;

[0082] S14, place the glassy carbon electrode (GCE) in 0.5 mol - In L-1 sulfuric acid solution, the glassy carbon electrode (GCE) was scanned several times from -0.3V to +1.5V by cyclic voltammetry (CV) until the curves completely overlapped, and then rinsed with ultrapure water and dried with nitrogen;

[0083] S15, in the presence of 0.1 mol-L -1 Potassium chloride (KCl) and 5mmol-L -1 Cyclic voltammetry (CV) was performed in a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferrate (K3[Fe(CN)]6) at -0.2 V to 0.6 V until the redox peaks were symmetrical and stable and the potential difference was about 90 mV.

[0084] S16, drop a total of 5.0 μL of graphitized carboxylated multi-walled carbon nanotubes vertically on the surface of a glassy carbon electrode (GCE), place it in a drying oven at 26°C until the surface is dry, then add 10 μL of an equal amount of a mixture of carbodiimide hydrochloride (EDC) / N-hydroxysuccinimide (NHS) dropwise, place it at 4°C for 2h, drop 5 μL of polydopamine (PDA) acetic acid solution on the electrode surface, dry it at room temperature, and obtain a graphitized carboxylated multi-walled carbon nanotube composite film;

[0085] S2, construction of electrochemical immunosensor platform;

[0086] S21, drop 10 μL of benz[a]anthracene antibody on the surface of graphitized carboxylated multi-walled carbon nanotube composite film, incubate in a 37°C drying oven for 2 h, then drop 5 μL of 3% bovine serum albumin (BSA) solution for 40 min to block the remaining active sites and avoid nonspecific adsorption, thereby allowing the immunosensor to specifically recognize benz[a]anthracene;

[0087] S22, placing the obtained immunosensor modified with the graphitized carboxylated multi-walled carbon nanotube composite film in a 4° C. environment for standby use;

[0088] S3, immunoassay steps for the detection of benz[a]anthracene;

[0089] S31, the immunosensor modified with graphitized carboxylated multi-walled carbon nanotube composite film was placed in 0.1 mol - L -1Potassium chloride (KCl) and 5mmol - L -1 In a PBS (pH = 7.0) buffer solution environment of tripotassium hexacyanoferrate (K3[Fe(CN)]6), the potential range was -0.2 to -0.6 V and the scan rate was 0.05 Vs -1 Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed under the conditions of to characterize the electrochemical performance and immune response of the modified immunosensor;

[0090] S32. Before measurement, 10 μL of different concentration gradients (0.1 ng-mL -1 ~100ng-mL -1 ) was titrated onto the modified immunosensor surface and incubated at 37 °C for 30 min;

[0091] S33, immersing the working electrode, the counter electrode and the reference electrode in the electrolyte, and recording the peak current Ip of different benz[a]anthracene concentrations between -0.2V and 0.6V by differential pulse voltammetry (DPV), wherein the amplitude is set to 50mV;

[0092] S34. A linear relationship is established by analyzing the relationship between Ip and the corresponding benzo[a]anthracene standard concentration to obtain a calibration curve.

[0093] Further, based on S2, at 0.1 mol - L -1 Potassium chloride (KCl) and 5mmol - L -1 In a PBS (pH=7.0) buffer solution environment of tripotassium hexacyanoferrate (K3[Fe(CN)]6), the electrochemical properties of different materials on the electrode surface were characterized by cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS).

[0094] Based on the above scheme: the glassy carbon electrode (GCE) detected a pair of stable and symmetrical redox peaks with a peak potential difference of 94mV and a peak current Ip of approximately 289.1μA, indicating that the electron transfer at the electrode interface is rapid, the prepared test substrate has good electron transfer properties, and is a good electron transfer medium. The peak current of the electrode modified with GR-MWCNTs-COOH increased significantly, reaching 404.3μA, which proves that GR-MWCNTs-COOH has good conductivity and electron transfer ability.

[0095] Furthermore, cyclic voltammetry was performed on the graphitized carboxylated multi-walled carbon nanotube / polydopamine / benzo[a]anthracene / bovine serum albumin / glassy carbon electrode at different scan rates. The peak current increased with the increase of scan rate and was in the range of 0.01-0.13 V.- s -1 In the scan rate range, the current and the square root of the scan rate show a good linear relationship, which indicates that the electron transfer in the electrode reaction is controlled by the diffusion process;

[0096] By Randles-Sevcik equation:

[0097] Ip=2.69×10 5 AD 1 / 2 n 3 / 2 v 1 / 2 c (1)

[0098] The effective surface area of ​​the electrode during the reaction can be calculated, where

[0099] Ip is the peak current (μA);

[0100] A is the effective surface area of ​​the electrode (cm 2 );

[0101] D is the diffusion coefficient (cm 2- s -1 );

[0102] n is the number of moles of transferred electrons in the electrostatic strain variation coefficient;

[0103] v is the rate of change of potential (Vs -1 );

[0104] c is the concentration of ferrocyanide (mmol - L -1 );

[0105] Where D = 0.72 × 10 -5 cm 2- s -1 , n=1,v=0.05V - s -1 , c = 5 mmol - L -1 The above formula is used to calculate that the effective areas of the glassy carbon electrode, the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes, and the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and polydopamine are 0.361, 0.505, and 1.053 cm2, respectively. It can be concluded that the synergistic effect of the two nanomaterials, graphitized carboxylated multi-walled carbon nanotubes and polydopamine, significantly increases the electrode surface area involved in the reaction and improves the sensitivity of the electrochemical detection method.

[0106] Based on the above scheme: verify whether the glassy carbon electrode has been successfully modified, and perform differential pulse voltammetry detection on the unmodified glassy carbon electrode, the electrode modified with graphitized carboxylated multi-walled carbon nanotubes, the electrode modified with polydopamine, and the electrode to which anti-benz[a]anthracene antibodies and bovine serum albumin were added respectively. On this basis, anti-benz[a]anthracene antibodies and bovine serum albumin were drop-coated one by one. Both anti-benz[a]anthracene antibodies and bovine serum albumin are proteins, which play an inhibitory role in the electron transfer process. Therefore, the peak current after differential pulse voltammetry detection decreases one by one. Based on the properties of the modified material and the detection mechanism, the successful modification of the glassy carbon electrode is verified.

[0107] Further, based on S3, 10 μL of anti-benz[a]anthracene antibody solution of different concentrations was incubated in the same experimental environment, and the anti-benz[a]anthracene antibody was drop-coated on the surface of the polydopamine nanoparticle composite film and placed in 0.1 mol - L -1 Potassium chloride (KCl) and 5mmol - L -1 Differential pulse voltammetry was performed in a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferrate (K3[Fe(CN)]6). As the concentration of anti-benz[a]anthracene antibody increased, the peak current gradually decreased. When the concentration of anti-benz[a]anthracene antibody was 100 μg-mL -1 , the peak current reached the lowest value, and then as the concentration of anti-benzo[a]anthracene antibody continued to increase, the peak current also increased. This is due to the limited active sites on the surface of the polydopamine nanoparticle composite membrane. The concentration of anti-benzo[a]anthracene antibody was 100 μg-mL -1 When the antibody concentration on the electrode surface reaches saturation, the concentration of anti-benz[a]anthracene antibody is 100 μg-mL -1 The optimal concentration for the experiment.

[0108] Based on the above scheme: The pH value of the supporting electrolyte in the buffer solution is an important factor affecting the performance of the immunosensor. It has a significant effect on the activity of anti-BaA and the amount of antibody fixed on the electrode surface. To determine the optimal pH value of the experiment, we prepared a series of electrolyte solutions with different pH values ​​and used differential pulse voltammetry (DPV) to determine the magnitude of their respective response currents. The peak current decreased as the pH increased from 4.0 to 7.0, reached a minimum at pH 7.0, and increased as the pH increased from 7.0 to 8.0. This is mainly because antibodies are proteins, and their structure and activity are very sensitive to pH. Under overly acidic or alkaline conditions, the antibody structure is prone to change, resulting in a decrease in its ability to bind to the target organic matter, which in turn affects the immune response. Therefore, PBS with a pH of 7.0 was used as the supporting electrolyte. K3[Fe(CN)6] was used as the redox probe of the electrode reaction in the immune response, and its concentration had a significant effect on the performance of the immunosensor. In order to obtain the optimal concentration of K3[Fe(CN)6], the response peak current changes before and after immunization were measured by cyclic voltammetry in buffer solutions containing different concentrations of K3[Fe(CN)6]. The potential range was -0.2 to 0.6 V, and the scan rate was 0.05 Vs -1 , K3[Fe(CN)6] buffer solutions (1, 5, 10 and 15 mmol - L -1 ), the immunosensor was incubated in the BaA solution at room temperature for 30 minutes, and four groups of CV comparison graphs before and after the reaction were obtained after detection, as shown in FIG. Fig.10 Where Ip is the curve before the reaction at the corresponding K3[Fe(CN)6] concentration, and Ip' is the curve after the reaction. Based on this, the current changes obtained before and after the reaction of buffer solutions with different concentrations were recorded and summarized, as shown in Table 1. 5mmol - L -1 The current change before and after the reaction was the largest at the concentration of K3[Fe(CN)6], and the oxidation current change rate and the reduction current change rate were 80.07% and 74.72%, respectively. Therefore, 5mmol - L -1 The concentration of K3[Fe(CN)6] was used as a redox probe.

[0109] Table 1 Changes in peak current before and after immunoreaction at different probe concentrations.

[0110]

[0111]

[0112] Further, based on S2, the detection principle of the electrochemical immunosensor is that the antibody-antigen reaction on the electrode surface causes changes in electron transfer, and the current generated on the electrode surface reflects the content of benz[a]anthracene. Therefore, when using differential pulse voltammetry for detection, the higher the benz[a]anthracene content in the sample to be tested, the lower the peak current. However, since benz[a]anthracene is a polycyclic aromatic hydrocarbon, it is easily electro-oxidized at high potential to promote electron transfer, which can increase the detection current and obtain a wider detection range. Therefore, the oxidation peak of differential pulse voltammetry is selected to quantitatively analyze the content of benz[a]anthracene. As an insulating electrical substance, benz[a]anthracene increases the transmission resistance during the immune reaction. Therefore, as the concentration of benz[a]anthracene increases, the peak current decreases. According to the fitting curve, it can be concluded that in the range of 5-100ng-ml- 1 In the range of , the response current is linearly related to the concentration of benz[a]anthracene, where the linear equation is I = 591.32-4.353C and the correlation coefficient is R 2 =0.996, in order to further derive the detection limit formula, the following deduction is made:

[0113] Standard Deviation:

[0114]

[0115] Assume that the detection limit concentration is C LOD , the corresponding measurement signal is

[0116] I LOD = k*C LOD +b (3)

[0117] Signal-to-Noise Ratio:

[0118]

[0119] When SNR = 3, that is,

[0120]

[0121] The detection limit formula can be calculated from the above formulas (2) to (5):

[0122]

[0123] in:

[0124] n is the number of parallel measurements of blank samples

[0125] I 0i is the blank sample signal value

[0126] k is the slope of the calibration equation

[0127] b is the intercept of the calibration equation

[0128] The blank sample was measured 11 times in parallel, and the detection limit was 0.35 ng-ml -1 , RSD = 0.52%, which is far lower than the international residual standard of benz[a]anthracene.

[0129] Based on the above scheme: Maowei Sea in Qinzhou City, Guangxi is a common estuary coastal area with Qinjiang River and Maoling River as the main inflow runoff. Water samples were collected from four different locations in Maowei Sea. After the samples were allowed to stand for 3 days, they were filtered through a 0.45μL microporous filter membrane and pretreated with ultraviolet light. The pH value was adjusted to neutral with NaOH, and the collected seawater was measured using GR-MWCNTs-COOH / PDA / anti-BaA / BSA. The experimental results are shown in Table 2. The recovery rate was between 94.18% and 99.11%, and RSD≤2.71%. The experimental results show that GR-MWCNTs-COOH / PDA / anti-BaA / BSA / GCE can be used to detect BaA in actual seawater.

[0130] Table 2 Results of real seawater determination using GR-MWCNTs-COOH / PDA / anti-BaA / BSA / GCE

[0131]

[0132]

[0133] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for detecting seawater-based BaA, characterized in that: The following steps are involved: S1, preparation of graphitized carboxylated multi-walled carbon nanotube-polydopamine composite modified electrode; S11, dissolving 0.03 g of polydopamine in a dilute acetic acid solution (1% v / v) to prepare a 0.03 mg-ml-1 polydopamine acetic acid solution, and storing it at 4° C. for later use; S12, dispersing 0.02 g of graphitized carboxylated multi-walled carbon nanotubes in 10 ml of PBS buffer at a pH of 7, centrifuging at 15000 r / min for 10 minutes in an ultracentrifuge at room temperature, then ultrasonicating in an ultrasonic oscillator for 1.5 hours, and stirring at room temperature for 1 hour; S13, polishing a glassy carbon electrode with a diameter of 3 mm with alumina powders of 1.0 μm, 0.3 μm, and 50 nm in diameter until the surface is bright, and then ultrasonically treated for 30 s; S14, place the glassy carbon electrode in 0.5mol-L-1 sulfuric acid solution, and use cyclic voltammetry from -0.3V ~ +1.5V was used to scan the glassy carbon electrode several times until the curves completely overlapped, and then it was rinsed with ultrapure water and dried with nitrogen; S15, in the presence of 0.1 mol-L -1 Potassium chloride and 5mmol-L -1 Cyclic voltammetry was used in a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferric acid at -0.2 V ~ 0.6 V for cyclic scanning until the redox peaks were symmetrical and stable and the potential difference was about 90 mV; S16, vertically drop a total of 5.0 μL of graphitized carboxylated multi-walled carbon nanotubes on the surface of the glassy carbon electrode, place it in a drying oven at 26°C until the surface is dry, then dropwise add 10 μL of an equal amount of a mixture of carbodiimide hydrochloride / N-hydroxysuccinimide, place it at 4°C for 2h, drop 5 μL of polydopamine (PDA) acetic acid solution on the electrode surface, dry it at room temperature, and obtain a graphitized carboxylated multi-walled carbon nanotube composite film; S2, construction of electrochemical immunosensor platform; S21, drop 10 μL of benz[a]anthracene antibody on the surface of graphitized carboxylated multi-walled carbon nanotube composite film, place in a 37°C drying oven for 2 h, then drop 5 μL of 3% bovine serum albumin solution for 40 min to block the remaining active sites and avoid nonspecific adsorption, thereby allowing the immunosensor to specifically recognize benz[a]anthracene; S22, placing the obtained immunosensor modified with the graphitized carboxylated multi-walled carbon nanotube composite film in a 4° C. environment for standby use; S3, immunoassay steps for the detection of benz[a]anthracene; S31, the immunosensor modified with graphitized carboxylated multi-walled carbon nanotube composite film was placed in 0.1 mol-L -1 Potassium chloride and 5mmol-L -1 In a PBS (pH = 7.0) buffer solution of tripotassium hexacyanoferrate, the potential range was -0.2 to -0.6 V and the scan rate was 0.05 Vs -1 Cyclic voltammetry and electrochemical impedance spectroscopy were performed under the conditions of to characterize the electrochemical performance and immune response of the modified immunosensor; S32. Before measurement, 10 μL of different concentration gradients (0.1 ng-mL -1 ~100ng-mL -1 ) was titrated onto the modified immunosensor surface and incubated at 37 °C for 30 min; S33, immersing the working electrode, the counter electrode and the reference electrode in the electrolyte, and recording the peak current Ip of different benz[a]anthracene concentrations between -0.2V and 0.6V by differential pulse voltammetry, wherein the amplitude is set to 50mV; S34. A linear relationship is established by analyzing the relationship between Ip and the corresponding benzo[a]anthracene standard concentration to obtain a calibration curve.

2. The method for detecting seawater-based BaA according to claim 1, characterized in that: Based on the S2, at 0.1 mol-L -1 Potassium chloride and 5mmol-L -1 In a PBS (pH=7.0) buffer solution environment of tripotassium hexacyanoferrate, the electrochemical properties of different materials on the electrode surface were characterized by cyclic voltammetry, differential pulse voltammetry, and electrochemical impedance spectroscopy.

3. The method for detecting seawater-based BaA according to claim 2, characterized in that: Cyclic voltammetry was performed on graphitized carboxylated multi-walled carbon nanotubes / polydopamine / benzo[a]anthracene / bovine serum albumin / glassy carbon electrode at different scan rates. The peak current increased with the increase of scan rate and was in the range of 0.01-0.13 Vs -1 In the scan rate range, the current and the square root of the scan rate show a good linear relationship, which indicates that the electron transfer in the electrode reaction is controlled by the diffusion process; By the Randles-Sevcik equation: Ip=2.69×10 5 AD 1 / 2 n 3 / 2 v 1 / 2 c (1) The effective surface area of ​​the electrode during the reaction can be calculated, where Ip is the peak current - μA; A is the effective surface area of ​​the electrode - cm 2 ; D is the diffusion coefficient - cm 2- s -1 ; n is the number of moles of transferred electrons in the electrostatic strain variation coefficient; v is the rate of change of potential - Vs -1 ; c is the concentration of ferrocyanide -mmol-L -1 ; Where D = 0.72 × 10 -5 cm 2- s -1 , n=1,v=0.05Vs -1 , c = 5mmol-L -1 The effective areas of the glassy carbon electrode, the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes, and the glassy carbon electrode modified with graphitized carboxylated multi-walled carbon nanotubes and polydopamine are calculated to be 0.361, 0.505, and 1.053 cm, respectively. 2 .

4. The method for detecting seawater-based BaA according to claim 3, characterized in that: To verify whether the glassy carbon electrode was successfully modified, differential pulse voltammetry was performed on the unmodified glassy carbon electrode, the electrode modified with graphitized carboxylated multi-walled carbon nanotubes, the electrode modified with polydopamine, and the electrodes to which anti-benz[a]anthracene antibodies and bovine serum albumin were added, respectively.

5. The method for detecting seawater-based BaA according to claim 1, characterized in that: Based on S3, 10 μL of anti-benz[a]anthracene antibody solutions of different concentrations were incubated in the same experimental environment, and the anti-benz[a]anthracene antibody was drop-coated on the surface of the polydopamine nanoparticle composite film and placed in a 0.1 mol-L -1 Potassium chloride and 5mmol-L -1 Differential pulse voltammetry scanning was carried out in a PBS (pH=7.0) buffer solution environment of tripotassium ferric hexacyanoferrate.

6. The method for detecting seawater-based BaA according to claim 1, characterized in that: Based on S2, the detection principle of the electrochemical immunosensor is that the antibody-antigen reaction on the electrode surface causes changes in electron transfer, and the current generated on the electrode surface reflects the content of benz[a]anthracene. Therefore, when using differential pulse voltammetry for detection, the higher the benz[a]anthracene content in the sample to be tested, the lower the peak current. However, since benz[a]anthracene is a polycyclic aromatic hydrocarbon, it is easily electro-oxidized at high potential to promote electron transfer, which can increase the detection current and thus obtain a wider detection range. Therefore, the oxidation peak of differential pulse voltammetry is selected to quantitatively analyze the content of benz[a]anthracene. As an insulating electrical substance, benz[a]anthracene increases the transmission resistance during the immune reaction. Therefore, as the concentration of benz[a]anthracene increases, the peak current decreases. According to the fitting curve, it can be concluded that in the range of 5-100ng-ml -1 In the range of , the response current is linearly related to the concentration of benz[a]anthracene, where the linear equation is I = 591.32-4.353C and the correlation coefficient is R 2 =0.996, in order to further derive the detection limit formula, the following deduction is made: Standard Deviation: Assume that the detection limit concentration is C LOD , the corresponding measurement signal is I LOD =k*C LOD +b (3) Signal-to-Noise Ratio: When SNR = 3, that is, The detection limit formula can be calculated from the above formulas (2) to (5): in: n is the number of parallel measurements of blank samples I 0i is the blank sample signal value k is the slope of the calibration equation b is the intercept of the calibration equation The blank sample was measured 11 times in parallel, and the detection limit was 0.35 ng-ml -1 , RSD = 0.52%, which is far lower than the international residual standard of benz[a]anthracene.